Perineal Lacerations: A Retrospective Study in a Habitual-Risk Public Maternity - Domenighi,Lauro Henrique Heinsch (2021)
Abstract Objective In around 85% of vaginal births, the parturients undergo perineal lacerations and/or episiotomy. The present study aimed to determine the incidence of lacerations and episiotomies among parturients in 2018 in a habitual-risk public maternity hospital in southern Brazil, and to determine the risk and protective factors for such events. Methodology A retrospective cross-sectional study. Data were obtained from medical records and analyzed using the Stata software. Univariate and multivariate logistic regressions were performed. Values of p<0.05 were considered significant. Results In 2018, there were 525 vaginal births, 27.8% of which were attended by obstetricians, 70.7% by obstetric nurses, and 1.5% evolved without assistance. Overall, 55.2% of the parturients had some degree of laceration. The professional who attended the birth was a significant variable: a greater number of first- and second-degree lacerations, as well as more severe cases, occurred in births attended by nurses (odds ratio [OR]: 2,95; 95% confidence interval [95%CI]: 1,74 to 5,03). Positions at birth that did not enable perineal protection techniques (expulsive period with the “hands-off” method), when analyzed in isolation, determined the risk; however, in the final regression model, this relationship was not confirmed. Although reported in the literature, there were no associations between the occurrence of laceration and age, skin color, or birth weight. In 24% of the births, episiotomy was performed, and doctors performed 63.5% of them. Conclusion Births attended by nurses resulted in an increased risk of perineal lacerations, of varying degrees. In turn, those assisted by physicians had a higher occurrence of episiotomy.